2011
DOI: 10.1080/09645292.2011.585794
|View full text |Cite
|
Sign up to set email alerts
|

The effect of student time allocation on academic achievement

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
2
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 23 publications
3
42
2
4
Order By: Relevance
“…Consequently, students in non-madrasah schools spend more time on national examination subjects (math, science, English, Indonesian). More teaching significantly enhances student performance (Stinebrickner & Stinebrickner, 2008), especially in mathematics and science (Grave, 2010). Consequently, we expect student achievement (in math, science, and English) in madrasahs to be lower than in non-madrasahs.…”
Section: School Track Differences and Student Achievementmentioning
confidence: 94%
See 2 more Smart Citations
“…Consequently, students in non-madrasah schools spend more time on national examination subjects (math, science, English, Indonesian). More teaching significantly enhances student performance (Stinebrickner & Stinebrickner, 2008), especially in mathematics and science (Grave, 2010). Consequently, we expect student achievement (in math, science, and English) in madrasahs to be lower than in non-madrasahs.…”
Section: School Track Differences and Student Achievementmentioning
confidence: 94%
“…With regard to investments in the primary process, the integrationists teach more hours, with 35 hr a week, compared to the traditionalists and the modernists, who each teach 30 hr. Teaching time is more productive than time spent on self-study (Dolton, Marcenaro, & Navarro, 2003), and more teaching time has been found to improve students' performance (Stinebrickner & Stinebrickner, 2008), particularly in mathematics and science (Grave, 2010).…”
Section: School Stream Differences and Student Achievementmentioning
confidence: 99%
See 1 more Smart Citation
“…The research on classroom attendance provides strong support for its role in increasing higher student grade performance (Caviglia-Harris, 2006;Credé, Roch, & Kieszczynka, 2010, Grave, 2011. This does not suggest that a mandatory attendance policy should be put into effect (Bai & Chang, 2015), since students may be using their time to fulfil other academic and non-academic commitments.…”
Section: Class Attendancementioning
confidence: 99%
“…Previous research has identified the impact of various factors on academic performance including motivation and identity (Briggs, Clark, & Hall, 2012;Fazey & Fazey, 2001;Haggis, 2004;Lizzio & Wilson, 2004;Smith & Oyserman, 2015), employment (Ford, Bosworth, & Wilson, 1995;Greene & Maggs, 2014;Nonis & Hudson, 2006;Wenz & Yu, 2010;Zoysa & Rudkin, 2007), and a combination of factors (e.g., age, prior education) (Britton & Tesser, 1991;Grave, 2011;Macan, Shahani, Dipboye, & Phillips, 1990;McKenzie & Schweitzer, 2001). Tertiary-level instructors and advisers may have little or no influence on altering students' characteristics or circumstances (e.g., age, prior education, employment); they may, however, be able to suggest or facilitate the adoption of different study behaviours that could lead to improvements in academic outcomes.…”
Section: Introductionmentioning
confidence: 99%